SKRINING TEKANAN DARAH DAN KADAR GULA DARAH SEBAGAI UPAYA DETEKSI DINI PENYAKIT TIDAK MENULAR PADA KADER KESEHATAN DI WILAYAH KERJA PUSKESMAS KOTA KEDIRI - Heny K.; Yunarsih; Nuritanilasari; Puguh; Sucipto (Suluh Adiluhung Publisher (SAPub), 2025)
Non-communicable diseases such as hypertension and diabetes mellitus remain major public health problems. This activity aims to detect the risk of non-communicable diseases early by checking blood pressure and blood sugar levels in health cadres in the work area of the Kediri City Community Health Center. The method used was direct blood pressure and blood sugar examination using a descriptive approach. The activity was conducted in September 2025 and was attended by 40 health cadres. The results of the activity showed that all cadres had blood pressure and blood sugar in the normal category. This activity increased cadres’ awareness of the importance of regular health checks as a preventive effort against non-communicable diseases.